Immigrants' Children Scientific Performance in a Double Comparative Design: The Influence of Origin, Destination, and Community - Jaap Dronkers; Manon de Heus (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
This paper studies the scientific literacy of immigrant children in a cross-classified multilevel framework. Using data from the 2006 PISA survey, features of immigrant children's countries of origin, countries of destination, and communities (the specific origin-destination combination) are taken into account in order to explain macro-level differences in immigrants' educational performance. Our sample consists of 9414 15-year-old immigrant children, originating from 46 different countries, living in 16 Western countries of destination. Results show that differences in scientific performance between immigrant children from different origins and between children living in different countries of destination cannot be fully explained by compositional differences. Contextual attributes of origin countries, destination countries, and communities matter as well. It is for instance shown that the better educational performance of immigrant children living in traditional immigration receiving countries cannot be explained by these children's favourable background characteristics. The political and economic features of the origin countries did not influence the science performance, in contrast with the origin countries' prevailing religions.
Keywords: 330; immigration; origin; destination; educational performance; PISA